Tigecycline and intravenous fosfomycin zone breakpoints equivalent to the EUCAST MIC criteria for Enterobacteriaceae - Pasteran, Fernando (2012)
Fil: Pasteran, Fernando. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Enfermedades Infecciosas. Departamento de Bacteriología. Servicio de Antimicrobianos; Argentina.